Social intelligence in the context of the european higher education area: Definición y relaciones con el ámbito educativo, social y futuro laboral - Sánchez Marín, Francisco José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The European Higher Education Area (EHEA) imposes a competency-based training model aimed at improving student training and responding to social and labor demands. This article aims to advance the theoretical knowledge of the constructs “interpersonal intelligence, social competence, emotional intelligence and social intelligence” and their relationship with future job performance, through a systematic literature review. A socially intelligent person can get along better with other people with whom he communicates or interacts.